In vitro inhibition of Neisseria gonorrhoeae growth by strict anaerobes. - Morin, A (1980)
Thirty two anaerobic bacterial strains were screened for their in vitro inhibitory activity toward 21 Neisseria gonorrhoeae strains, including two penicillin-resistant strains. From this screening, six anaerobic bacteria belonging to the genera Bacteroides, Peptostreptococcus, and Eubacterium were selected for their large antigonococcal spectrum of activity. The inhibitory activity of these six strains appears to be specific to the gonococcus as a variety of anaerobes and aerobes were not generally inhibited by these strains. The antigonococcal effect was not due to pH change or nutrient depletion of the media.